1997
DOI: 10.1021/jf960483j
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Differentiation of Maize Hybrid Stovers Using Analytical Pyrolysis and High-Performance Liquid Chromatography

Abstract: Pyrolysis/gas chromatography/mass spectrometry (PY/GC/MS) and high-performance liquid chromatography with electrochemical detection (HPLC-ED) were carried out on stover samples from ten commercial maize hybrids grown in northern Italy. The objective was to check whether the composition of the cell wall lignin and polysaccharides, as obtained by PY/GC/MS, and the phenolic acid content, as determined by HPLC-ED, were significantly different in the various hybrids. Neutral detergent fiber (NDF) and crude protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
1
6
0
1
Order By: Relevance
“…However, the mass percent of extractives varied by almost a factor of 2 between samples (Table 2). While a detailed explanation of compositional variation among stover samples is beyond the scope of this work, previous studies have demonstrated differing chemical composition in various stovers derived from maize hybrids (14) and between different anatomical fractions (i.e., leaves, cobs, husks, and stalks) of corn plants (3) and corn stover (15). Crop maturity (3) and storage method 2 are consistent with previous analyses of extractives in herbaceous biomass (9).…”
Section: Resultssupporting
confidence: 83%
“…However, the mass percent of extractives varied by almost a factor of 2 between samples (Table 2). While a detailed explanation of compositional variation among stover samples is beyond the scope of this work, previous studies have demonstrated differing chemical composition in various stovers derived from maize hybrids (14) and between different anatomical fractions (i.e., leaves, cobs, husks, and stalks) of corn plants (3) and corn stover (15). Crop maturity (3) and storage method 2 are consistent with previous analyses of extractives in herbaceous biomass (9).…”
Section: Resultssupporting
confidence: 83%
“…Analytical pyrolysis has been used to characterize the structure of organic N compounds in soils [13][14][15], as well as protein and fiber content in ruminant feedstuffs and corn stover [16][17][18][19][20]. The technique allows for sensitive, fast and precise identification of N-containing pyrolysis products.…”
Section: Introductionmentioning
confidence: 99%
“…Análise de materiais poliméricos, como taninos, lignina, 85,86 carboidratos presente em forragens 87 e amostras de híbridos de milho foram estudados por Galleti et al. 88 O trabalho resultou no estudo da composição química desses híbridos, o que possibilitou encontrar quatro produtos de pirólise representativos (2-furaldeído, fenol, guaiacol e 2,6-dimetoxifenol), denominados marcadores, que permitiram diferenciar as amostras estudadas.…”
Section: Alimentos E Produtos Relacionados à Agriculturaunclassified